(untitled) (Bangladesh Journal of Pharmacology, 2013)
Convolvulus arvensis is traditionally used as laxative. Its decoction is used in cough, flu, jaundice and in skin diseases. It is also used to treat the painful joints, inflammation and swelling. The current study was conducted to determine its hepatoprotective activity. The results showed that extract of C. arvensis (200 mg/kg and 500 mg/kg) produced significant (p<0.05) decrease in paracetamol induced increased levels of liver enzymes and total bilirubin. Histopathological investigation and detection of active constituent, qurecetin by HPLC also supported the results. So the current study showed that ethanolic extract of C. arvensis possess hepatoprotective activity.